2014
DOI: 10.1364/ol.39.006383
|View full text |Cite
|
Sign up to set email alerts
|

16  μm emission based on linear loss control in a Er:Yb doped double-clad fiber laser

Abstract: Based on the control of the linear losses of the cavity, we demonstrate the possibility to achieve filterless laser emission above 1.6 μm, from a C-band double-clad Er:Yb doped fiber amplifier. The concept is validated in both continuous wave and mode-locked regimes, using a figure-of-eight geometry. A unidirectional ring cavity is also tested in the continuous regime. Spectral properties of laser emissions are characterized as a function of the intracavity linear losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…As said in the introduction, low cavity loss maybe helpful to realize long wavelength operation. We have successfully used this approach to realize a figure-of-eight laser operating above 1.6 µm [32]. Here, long wavelength emission at 1.61 μm was also obtained because of the low cavity loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As said in the introduction, low cavity loss maybe helpful to realize long wavelength operation. We have successfully used this approach to realize a figure-of-eight laser operating above 1.6 µm [32]. Here, long wavelength emission at 1.61 μm was also obtained because of the low cavity loss.…”
Section: Resultsmentioning
confidence: 99%
“…Then L-band mode locked fiber lasers have attracted much attention in recent years [28][29][30][31]. We have recently shown that the control of the linear losses of the cavity in a filterless figure-of-eight laser allows to obtain continuous wave regime or mode-locked operation above 1.6 µm [32]. Following this principle we have built a unidirectional ring cavity passively mode-locked with graphene saturable absorber (GSA) operating above 1.6 µm.…”
Section: Introductionmentioning
confidence: 99%
“…In essence, the method for realizing L-band emission in EDFs is to limit population inversion at a low level (~30%-40%) [18]. In this case, the EDF can provide a positive gain at 1600 nm, but negative at 1550 nm.…”
Section: Experimental Setup and Principlementioning
confidence: 99%
“…L-band MLFLs can widen the transmission capacity of optical communications and also find various applications in spectroscopy, biomedical diagnostics and surgery [17][18][19]. It has been known that the emission wavelength of lasers depends on the linear cavity loss, fiber length and dopant concentration [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation